Incentive efficiency of compensation based on accounting and market performance - Kim, Oliver; Suh, Yoon (Journal of Accounting and Economics, 1993)
This paper analyzes how earnings and price are used in executive compensation contracts. Risk-averse shareholders collectively design a contract and individually trade in the stock market. In the optimal linear contract the use of earnings and price depends critically on incentive efficiency, i.e., how precisely the measures convey the true outcome. The relative weight of price to earnings exaggerates the true relative importance of price because price impounds traders' overall information while its informational value lies in the incremental information it provides. The use of price allows shareholders to share trading risks with managers.